If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7t + -2) + -1(-3t + 1) = 3(1 + -3t) Reorder the terms: (-2 + 7t) + -1(-3t + 1) = 3(1 + -3t) Remove parenthesis around (-2 + 7t) -2 + 7t + -1(-3t + 1) = 3(1 + -3t) Reorder the terms: -2 + 7t + -1(1 + -3t) = 3(1 + -3t) -2 + 7t + (1 * -1 + -3t * -1) = 3(1 + -3t) -2 + 7t + (-1 + 3t) = 3(1 + -3t) Reorder the terms: -2 + -1 + 7t + 3t = 3(1 + -3t) Combine like terms: -2 + -1 = -3 -3 + 7t + 3t = 3(1 + -3t) Combine like terms: 7t + 3t = 10t -3 + 10t = 3(1 + -3t) -3 + 10t = (1 * 3 + -3t * 3) -3 + 10t = (3 + -9t) Solving -3 + 10t = 3 + -9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '9t' to each side of the equation. -3 + 10t + 9t = 3 + -9t + 9t Combine like terms: 10t + 9t = 19t -3 + 19t = 3 + -9t + 9t Combine like terms: -9t + 9t = 0 -3 + 19t = 3 + 0 -3 + 19t = 3 Add '3' to each side of the equation. -3 + 3 + 19t = 3 + 3 Combine like terms: -3 + 3 = 0 0 + 19t = 3 + 3 19t = 3 + 3 Combine like terms: 3 + 3 = 6 19t = 6 Divide each side by '19'. t = 0.3157894737 Simplifying t = 0.3157894737
| 6x-7=4x+39 | | 13=3x+8 | | 64-13(8-4)= | | 6x/3=2 | | 12(2-x)=6(1+x) | | 3(4x+2)-3= | | 9x+4=7x-2 | | -6x=3x^2+9 | | 0=-16t^2+28t-32 | | 6*7= | | 2=7+4b | | 0+(50*1)-60-(60*0)+10= | | 28-7x=-70 | | -6=3x^2+9 | | 576334s*246578874s= | | 3(x+2)*(3x+6)=0 | | 17-3= | | 3x-17=7x-5(x-2) | | 11x-18=x^2 | | d^2+10d+25=0 | | 49b^2-16=0 | | 8-2x=-2 | | 31=4x+5 | | -3/4+1/4=1/2 | | 2(x-6)+3x=2(x+2)-x | | 3y^2-1=-2y | | s^2+6s+8=0 | | 4x^2+12x-27=0 | | 2x^2=-7x-29 | | 5x-2x=2x+2 | | 42-3x=21 | | 2(x-6)+3x=2(x-5) |